Prevalence, transitions and factors predicting transition between frailty states among rural community-dwelling older adults in Malaysia - Ahmad, Nur Sakinah; Hairi, Noran Naqiah; Said, Mas Ayu; Kamaruzzaman, Shahrul Bahyah; Choo, Wan Yuen; Hairi, Farizah Mohd; Othman, Sajaratulnisah; Ismail, Norliana; Peramalah, Devi; Kandiben, Shathanapriya; Ali, Zainudin Mohd; Ahmad, Sharifah Nor; et al. (Public Library of Science, 2018)
Objectives This study aims to describe the prevalence and transitions of frailty among rural-community dwelling older adults in Malaysia and to analyse factors associated with different states of frailty transition. Frailty was conceptualized using modified Fried phenotype from the Cardiovascular Health Study. Design This is a prospective longitudinal study with 12-months follow up among older adults in Malaysia. Setting Kuala Pilah, a district in Negeri Sembilan, which is one of the fourteen states in Malaysia. Participants 2,324 community-dwelling older Malaysians aged 60 years and older. Results The overall prevalence of frailty in this study was 9.4% (95% CI 7.8–11.2). The prevalence increased at least three-fold with every 10 years of age. This increase was seen higher in women compared to men. Being frail was significantly associated with older age, women, and respondents with a higher number of chronic diseases, poor cognitive function and low socioeconomic status (p<0.05). During the 12-months follow-up, our study showed that the transition towards greater frailty states were more likely (22.9%) than transition toward lesser frailty states (19.9%) while majority (57.2%) Remained unchanged. Multivariate logistic regression analysis showed that presence of low physical activity increased the likelihood of worsening transition towards greater frailty states by three times (OR 2.9, 95% CI 2.2–3.7) and lowered the likelihood of transition towards lesser frailty states (OR 0.3, 95% CI 0.2–0.4). Conclusion Frailty is reported among one in every eleven older adults in this study. The prevalence increased across age groups and was higher among women than men. Frailty possesses a dynamic status due to its potential reversibility. This reversibility makes it a cornerstone to delay frailty progression. Our study noted that physical activity conferred the greatest benefit as a modifiable factor in frailty prevention.